Application of Intracranial Pressure-Directed Therapy on Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Yang, Jun; Lu, Junlin; Li, Runting; Lin, Fa; Chen, Yu; Han, Heze; Yan, Debin; Li, Ruinan; Li, Zhipeng; Zhang, Haibin; Yuan, Kexin; Li, Hongliang; et al. (Frontiers in Aging Neuroscience, 2022)
Objective Elevated ICP is a well-recognized phenomenon in aneurysmal subarachnoid hemorrhage (aSAH) that has been demonstrated to lead to poor outcomes. Delayed cerebral ischemia (DCI) is the most important reason for a poor clinical outcome after a subarachnoid hemorrhage. DCI is understood as a multifactorial process that evolves over time, largely caused by the sequelae of increased intracranial pressure (ICP). The study aimed to assess how to better define the association between ICP and DCI, and whether rational ICP management can improve the outcome of aSAH patients. Methods We prospectively reviewed patients diagnosed with aSAH and received microsurgery clipping at our department from December 2019 to January 2021. Subdural ICP monitoring devices were kept to monitor the ICP. The ICP values were recorded every 1-h epochs. ICP -guided dehydration treatments were routinely performed to control the ICP level of patients after surgery. To evaluate whether the subdural ICP-directed management improved the prognosis of the aSAH patients, we compared the outcome data of the patients in our cohort with those treated at another ward of our hospital at the same period. Results In total, 144 consecutive aSAH patients received microsurgery clipping at our department, 68 of whom underwent ICP monitoring. A total of 11,424 1-h ICP measurements were recorded for the included patients (1.30 years of recordings). Of 68 patients with ICP monitoring, 27 (27/68, 39.7%) patients developed DCI. Univariate analysis showed that higher Hunt-Hess grade (OR 2.138, 95% CI 1.025–4.459, p = 0.043), higher preoperative modified Rankin Scale score (OR 1.534, 95% CI 1.033–2.276, p = 0.034), and the max ICP value of each day value >28.5 mmHg (OR 4.442, 95% CI 1.509–13.082, p = 0.007) were associated with DCI. Also, patients with ICP-directed treatment showed a significantly lower DCI incidence than patients without ICP monitoring. Conclusion Our study suggests that I less than 15 mmHg possibly constitute normal values and that 28.5 mmHg is the ICP threshold most strongly associated with the occurrence of DCI in aSAH patients. Patients who received the ICP-directed treatment presented a lower incidence of DCI. Our findings provide a basis for the recommendation of ICP-directed treatment after aSAH. Trial Registration Number NCT04785976.